REKONSTRUKSI PEMIKIRAN PENDIDIKAN ISLAM: PERSPEKTIF TRANSFORMASI SOSIAL DAN KONTEMPORER - Hamida Olfah (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study is to determine how Islamic education influences the transformation of society. The research technique is library research. One of the strategies and frameworks for improving human life in all areas of life is education. Islam, a religion that is full of compassion for all living things, is very aware of the state of society. The establishment of Arab society by the Prophet Muhammad SAW is shown by historical evidence. Arab society then continued to develop until Islam spread globally. Since education is one of the most effective ways to improve human growth, the results of this study indicate that Islam uses it to build society.